2015
DOI: 10.3349/ymj.2015.56.3.812
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Thyroid Gland Involvement in Hypopharyngeal Squamous Cell Carcinoma

Abstract: PurposeDecision to perform concurrent ipsilateral thyroidectomy on patients with hypopharyngeal cancer is important, and unnecessary thyroidectomy should be avoided if oncologically feasible. We hypothesized that concurrent ipsilateral thyroidectomy is not routinely required to prevent occult metastasis. This study aimed to determine the prevalence of histological thyroid invasion in patients with hypopharyngeal cancer, and to refine the indications for prophylactic ipsilateral thyroidectomy in patients with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The overall rate of thyroid invasion in head and neck SCC is likely higher as not all such cancers are treated by surgery, and thyroidectomy is not routinely performed even in the resection of these cancers (10-13). Moreover, thyroid function was not routinely reported in most studieswith occasional mention of patients being euthyroid or hypothyroid perioperatively (12)(13)(14). Thus, the rate of hyperthyroidism in patients with thyroid invasion secondary to head and neck SCC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The overall rate of thyroid invasion in head and neck SCC is likely higher as not all such cancers are treated by surgery, and thyroidectomy is not routinely performed even in the resection of these cancers (10-13). Moreover, thyroid function was not routinely reported in most studieswith occasional mention of patients being euthyroid or hypothyroid perioperatively (12)(13)(14). Thus, the rate of hyperthyroidism in patients with thyroid invasion secondary to head and neck SCC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, ipsilateral hemithyroidectomy or total thyroidectomy was considered mandatory for all patients undergoing total laryngectomy [22]. However, several patients who underwent laryngectomies with partial preservation of the thyroid gland still developed hypothyroidism because the blood supply to the remnant thyroid gland was compromised during the operation [23]. Moreover, later studies have shown that thyroid gland invasion is uncommon [22][23][24].…”
Section: Thyroid Gland Preservationmentioning
confidence: 99%
“…Chang et al in a study of 49 patients with hypopharyngeal carcinoma found that preoperative CT imaging was the only statistically significant predictive factor for TGI (p=0.034). 19 Intraoperative assessment of the thyroid gland by palpation is also useful in detecting synchronous lesions involving the thyroid gland. 20 In our series, incidental presence of papillary thyroid carcinoma was found in 3 thyroid specimens.…”
Section: 18mentioning
confidence: 99%